Synergy of Banana Starch and Moringa Leaves in Maintaining Hemoglobin Homeostasis and Body Weight in Dextran Sodium Sulfate-Induced Rats - Nova Romadhona; Fifi Luthfiyah; Dwipajati (Poltekkes Kemenkes Mataram, 2026)
Background: Colonic inflammation can be triggered by gastrointestinal infections and by chemical agents such as Dextran Sodium Sulfate (DSS). Elevated glucose levels increase insulin resistance and raise circulating insulin-like-growth factor-1 (IGF-1), which may contribute to cancer risk. One possible approach to modulating this condition is through prebiotics contained in kepok banana, because its inulin and resistant starch act as natural prebiotics. Research Purposes: This study aimed to analyze the effect of kepok banana and moringa leaf-based prebiotics on random blood glucose levels in Wistar rats exposed to Dextran Sodium Sulfate (DSS). Research Methods: This true experimental study used a Randomized Block Design (RBD) with five treatment groups and six rats per group. Blood glucose levels were analyzed using one-way ANOVA with a 95% confidence level. Data on feed intake and intake of the kepok banana–moringa starch were analyzed using the Kruskal-Wallis test at a 95% confidence level. Research Result: Administration of kepok banana–moringa starch in DSS-induced rats did not significantly affect feed intake or reduce blood glucose levels (p=0.121). The most favorable response was observed in P2 group 0.05 g/rat), which showed a tendency toward lower blood glucose levels in DSS-induced rats. Conclusion: Kepok banana–moringa starch administration did not significantly reduce blood glucose levels in DSS-induced rats, although the P2 dose showed a tendency toward improvement.